Genetic variability of Mexican serviceberry (Malacomeles denticulata [Kunth] Jones) obtained by inter simple sequence repeated or intermicrosatellites (ISSR) markers - González-Cerritos, Daniela; Núñez-Colín, Carlos Alberto; Villordo-Pineda, Emiliano; Medina-Ramos, Gabriela; González-Chavira, Mario Martín (Acta Universitaria, 2015)
Malacomeles denticulata is a native fruit of Mexico that recently had been reported functional proprieties to be proposed as a fruit option. This research aims to elucidate the variability of twelve populations of M. denticulata by Inter Simple Sequence Repeated or Inter-microsatellites (ISSR) markers. All ISSR showed high values of Polymorphic Information Content (PIC) and Nei’s Index of Population Differentiation (GST) as well as high percentage of polymorphism. Three groups of variability were conformed, where seven populations of Guanajuato and the population of El Tepozán, Querétaro conformed the first group; while the populations of Agua Zarca (Guanajuato), La Joya (Querétaro), and Santa Catarina del Monte (México) conformed the other group. Finally, the population of San Miguel Tlaixpan (México) was separated as outlier group. According to Analysis of Molecular Variance (Amova), the within population variability was 47% and among population variability was 53% of total variability, that agree on the variability of seed traits but disagree on the variability of SSR markers.
Keywords: Array; Array; Array; Array